Educational Elements and Logical Structures of Information Modeling Education in the Context of Creating Digital Educational Resources - Siradjev Saloxiddin Negmatovich (Genius Journals, 2022)
This article presents educational elements and logical structures of Information Modeling education in the context of creating digital educational resources. In addition, factors are presented that ensure the internal structure of the content of education in its integrity and relative independence
Keywords: Digital education, information modeling, educational elements of Education, logical structures